Some new brachypterous cockroaches (Blattodea: Blaberidae: Epilamprinae) from the Philippines - Lucañas, Cristian C. (Zootaxa, 2017)
A new genus and species of brachypterous cockroach, Decoralampra fulgencioi gen. et sp. nov. is described from the Philippines. On the basis of the abbreviated tegmina and bristles of the folded structure of left phallomere, it is hypothesized to be close to the genus Cyrtonotula Uravov 1939 and Howintoniella Roth 1981. Also a new species, C. maquilingensis sp. nov. is described. This is the fourth species of the genus and the first to be recorded in the Philippines.